Analisis Butir Soal Higher Order Thinking Skills (HOTS) Pada Soal Ujian JLPT N4 - Trisgar, Trisgar; Juangsih, Juju; Herniwati, Herniwati (KIRYOKU, 2023)
Supporting the realization of the nation's golden generation in 2045 with productive, creative, innovative and affective characteristics, one way to hone these abilities is to provide questions based on HOTS. However, it is known that many Japanese exam questions are not based on HOTS. Because of this, the author is interested in examining more deeply the questions on JLPT N4 exam sheet, so that it can be used as a reference in making HOTS-based Japanese exam questions. This qualitative research using descriptive method and collecting data using documentation techniques. The problem in this research is: 1) How is the implementation of the HOTS and LOTS-based questions on the JLPT level N4 test sheet?, 2) What are the characteristics and forms of the HOTS and LOTS-based questions? To answer the problem formulation above, the author uses the revised edition of Bloom's theory regarding cognitive levels and the theory of the Kemendikbud (2017) regarding the implementation of HOTS. The results showed that the percentage of questions that implemented HOTS was 43% and 57% LOTS out of a total of 70 multiple choice questions only. The characteristics of the HOTS questions is measure higher-order thinking skills and are based on contextual problems.